2005
DOI: 10.1111/j.1365-2036.2005.02338.x
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide as maintenance treatment in Crohn's disease: a placebo‐controlled trial

Abstract: SUMMARYAim: To assess the efficacy and safety of budesonide capsules 6 mg daily for prolongation of time to relapse and maintenance of remission in patients with Crohn's disease (CD) affecting the ileum and/or ascending colon. Methods: In a double-blind, placebo-controlled, multicentre trial, 110 patients with CD, who had previously achieved remission in a placebo-controlled trial of budesonide 9 mg daily, were randomly assigned to receive budesonide 6 mg once daily or placebo for 52 weeks. Primary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 26 publications
1
53
0
2
Order By: Relevance
“…A further trial investigating oral pH-modified-release budesonide also found that budesonide was not effective for maintaining steroid-induced remission compared with placebo (Table 1) [Gross et al 1998]. Finally, a trial investigating modifiedrelease budesonide showed that budesonide and placebo had similar relapse rates after 1 year of treatment (Table 1) [Hanauer et al 2005].…”
Section: Efficacy In Crohn's Diseasementioning
confidence: 99%
“…A further trial investigating oral pH-modified-release budesonide also found that budesonide was not effective for maintaining steroid-induced remission compared with placebo (Table 1) [Gross et al 1998]. Finally, a trial investigating modifiedrelease budesonide showed that budesonide and placebo had similar relapse rates after 1 year of treatment (Table 1) [Hanauer et al 2005].…”
Section: Efficacy In Crohn's Diseasementioning
confidence: 99%
“…The results of these trials show that budesonide is comparable to prednisone in inducing clinical remission in patients with ileo-colonic CD [31]. However, it is not significantly more effective than placebo [21,32,33,34,35,36,37,38,39] or systemic corticosteroids [40] in maintaining clinical remission in CD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, preliminary data from ongoing trials show that budesonide MMX 9 mg has a good tolerability: steroid-related side effects were reported by 5.5% of patients and consisted of moon face, mood and sleep changes. Hanauer et al [39] showed that plasma cortisol was slightly decreased in patients administered budesonide MMX, but the cortisol levels of the majority of patients remained within acceptable limits (unpubl. data: Randomized Placebo Controlled Trial of Budesonide-MMX™ 6 and 9 mg in Patients with Ulcerative Colitis: http://clinicaltrials.gov/ct2/show/NCT00679380).…”
Section: Resultsmentioning
confidence: 99%
“…Budesonide: Lower doses of budesonide (3 or 6 mg) have also been studied for their potential to be effective in the maintenance of remission. Although earlier metaanalyses have not shown that budesonide was superior over placebo [16,48] , a recent randomized, placebo-controlled trial found a trend towards a longer quiescent disease in budesonide treated patients compared to placebo [49] . In this trial, no significant difference in total adverse events or corticosteroid-associated events was demonstrated between placebo and budesonide.…”
Section: Maintenance Of Remissionmentioning
confidence: 99%